Analisis Pertumbuhan Penumpang di Bandar Udara Gamar Malamo Galela Kabupaten Halmahera Utara Provinsi Maluku Utara - Rahim, Jamaluddin; Sabur, Fatmawati (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2018)
Gamar Malamo Galela Airport in Maluku Province. Flight services on the route Ternate - Galela PP by PT. Merpati Nusantara Airlines uses Twin Otter or DHC-6 aircraft, with a frequency of 3 times a week. This research is a non-experimental research and case study of an increase in demand for transportation services. Data processing uses quantitative and quantitative description approach based on secondary data through forecasting the number of aircraft movement requests. data processing using the SPSS 22 series program, forecasting the projected number of passenger movements. The results of the study are based on time sires data on the population growth variable showing the results of the Linear Regression Equation variable Y value = 2232.5 + 2841.1 X, with the coefficient of determination is R² = 0.653, while the Logarithmic model with a value of Y = 3205.823+ Ln (7885 , 107X) with the acquisition value of determination R ² = 0.813, Polynomial (cubic), with the acquisition of the value of equation Y = -20691.2 + 29790,952 X - 8512.5 X2 + 773.58 X3, with the determination determination R ² = 0.94 , the exponential model produces the equation Y = 187.871 e0.213x with the detremination value R2 = 0.603. Where the number of passengers demand for air transportation services at Gamar Malamo Airport in 2040 reached 238,179 people